2021
DOI: 10.3389/fpubh.2021.741345
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Diagnostic Uncertainty in Antibiotic Prescribing: A Latent Class Study of Primary Care Physicians in Hubei China

Abstract: Background: Misuse of antibiotics is prevalent worldwide and primary care is a major contributor. Although a clear diagnosis is fundamental for rational antibiotic use, primary care physicians often struggle with diagnostic uncertainty. However, we know little about how physicians cope with this situation and its association with antibiotic prescribing.Methods: A total of 583 primary care physicians were surveyed using the Dealing with Uncertainty Questionnaire. Their prescriptions (n = 949,181) over the year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The empiric use of antibiotics was also more likely among GPs when there was diagnostic uncertainty, similar to the findings from recent studies from a number of other countries [ 106 , 107 , 108 , 109 ]. Prescribing antibiotics when there is uncertainty between possible viral or bacterial infections is exacerbated when laboratory tests are expensive, there is a lack of access to them as well as a lack of sensitive and cost-effective point-of-care testing equipment within LMIC settings [ 16 , 17 , 110 , 111 ].…”
Section: Discussionsupporting
confidence: 86%
“…The empiric use of antibiotics was also more likely among GPs when there was diagnostic uncertainty, similar to the findings from recent studies from a number of other countries [ 106 , 107 , 108 , 109 ]. Prescribing antibiotics when there is uncertainty between possible viral or bacterial infections is exacerbated when laboratory tests are expensive, there is a lack of access to them as well as a lack of sensitive and cost-effective point-of-care testing equipment within LMIC settings [ 16 , 17 , 110 , 111 ].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, surveillance of antibiotic use should also distinguish conditions for which antibiotic treatment is always justified to avoid underuse of antibiotics in certain cases. 16 , 57 Finally, our finding indicates the need for a long-term, nationwide, government intervened, cross-sectoral antimicrobial stewardship program to promote evidence-based antibiotic use and enhance the consistency in the quality of healthcare services throughout China. 36 …”
Section: Discussionmentioning
confidence: 78%
“…Respondents reported that URTIs were the most common reason for patients visiting township hospitals and village clinics, which is in line with previous studies in rural China [ 38 , 39 ], and that URTIs are the major diagnosis for which antibiotics are prescribed. Although the vast majority of URTIs are self-limiting, meaning it is usually possible to ‘wait and see’, few respondents reported adopting the strategy [ 25 ]. Respondents reported that, due to diagnostic and prognostic uncertainty, they prescribe antibiotics just in case, aiming to mitigate the perceived risk of complications (such as hospital admission).…”
Section: Discussionmentioning
confidence: 99%
“…Significant research on clinical uncertainty in other settings worldwide has been conducted, strongly indicating that clinical uncertainty is associated with higher levels of antibiotic prescribing [ 1 , 21 , 25 ]. The specific reasons for clinical uncertainty are often context- and culture-specific, and understanding how clinical uncertainty influences clinician practices concerning antibiotic use in rural China is currently limited.…”
Section: Introductionmentioning
confidence: 99%